Commentary: ethnography, critique and the state. Some thoughts on "fiscal anthropological insights into the heart of contemporary statehood"1. Issue 3 (2nd September 2018) - Bierschenk, Thomas
Abstract: This commentary explores the assets and liabilities of anthropology for the study of core functions of statehood (such as taxation) that increasingly become a matter of transnational negotiation and norm-making. It takes issue with some anthropologists' counter-hegemonic self-positioning, calling upon anthropologists to think harder about the conditions and challenges of studying highly formalized expert knowledge and the epistemological reflection this requires.